Independent Curriculum Teaching Module Writing Training Based on Differentiated Learning: Penelitian - Syahrul R; Ayu Gustia Ningsih; Yenni Hayati; Yulianti Rasyid; Mita Domi Fella Henaggil (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study was to describe the transformation of teacher competency in developing Independent Curriculum teaching modules based on differentiated learning at SMA Negeri 1 Harau Regency. The transformation from Curriculum 2013 (K13) to Independent Curriculum requires teachers to adjust their learning tools, replace the Learning Implementation Plan (RPP) with a Teaching Module. This training was organized by a community service team from Lecturers of the Regional Indonesian Language and Literature Department and involved 75 teachers. This program includes an explanation of the introduction of student characteristics, understanding the concept of differentiated learning, and strategies for writing teaching modules that integrate these principles. Interactive discussions, direct practice, reflection, and pre-test and post-test evaluations through the Quizizz application were used. The results of the analysis showed an increase in teacher understanding and skills in implementing differentiated learning when designing learning modules. The learning modules produced after the training proved to be more integrated with the principles of differentiated learning compared to the previous version.